Synthesis of Nitrogen- and Oxygen-Containing Heterocycles Catalysed by Metal Nanoparticles Reported in 2022 - Dhameliya, Tejas M.; Shah, Disha D.; Shah, Aayushi C.; Shah, Tithi S.; Patel, Tanvi M.; Rana, Devalben K.; Sureja, Dipen K.; Bodiwala, Kunjan B. (Synlett, 2024)
The versatility of aza- and oxa-heterocyclic compounds has garnered significant attention in recent times. A large number of currently approved pharmaceutical products include nitrogen- and oxygen-containing heterocycles. Recent nanotechnological developments have propelled an upsurge in the applications of nanocatalysis for heterocyclic synthesis. Metal nanoparticles (MNPs) have emerged as promising catalysts for the synthesis of aza- and oxa-heterocycles owing to their unique physicochemical properties. Various MNPs including gold, silver, nickel and palladium have been evaluated for their catalytic activities in different reaction types, including cyclisation, coupling, hydrogenation and oxidative transformations. The MNPs have exhibited remarkable catalytic efficiency when utilised under optimal conditions. These catalysts have showcased high reusability and recyclability, yielding satisfactory amounts of the desired heterocyclic compound. The present work provides a detailed overview of recent advances in the area of MNP-assisted synthetic construction of aza- and oxa-heterocycles, published during the previous calendar year, 2022. The review serves as a valuable resource and also paves the way for future investigations in the development of novel catalytic strategies for heterocycle synthesis.1 Introduction2 Nanocatalysis3 Aza- and Oxa-Heterocycle Synthesis Catalysed by MNPs3.1 AuNPs3.2 CuNPs3.3 CoNPs3.4 FeNPs3.5 NiNPs3.6 PdNPs3.7 PtNPs3.8 SiNPs3.9 ZnNPs3.10 Bimetallic NPs3.11 Other MNPs4 Summary and Outlook
Keywords: heterocycles; nanocatalysts; MNPs; aza-heterocycles; oxa-heterocycles; synthesis